ANALYSIS THE EFFECT OF PERSONAL SELLING AND DIRECT MARKETING ON DECIONS OF EASY WADIAH SAVING CUSTOMERS AT KC 2 MAKASSAR BANK SYARIAH INDONESIA (Tbk) - Arnandha, Genelly Putri (Scientia integritas Utama, 2022)
The purpose of this research is to examine the impact of personal selling and digital marketing on easy wadiah savings at KC 2 Makassar Bank Syariah Indonesia (Tbk). The research data was derived from the responses of 319 Kc 2 Makassar Bank Syariah Indonesia customers to a questionnaire about their decisions to save on easy wadiah savings in 1 month. The data collection method employs a questionnaire that has been validated and reliable. The results of this research indicate that (1) personal selling and direct marketing have a 0.723 effect on decisions. Personal selling and direct marketing can represent 72.3% of the variety of saving decisions in this case. (2) A simultaneous test of the hypothesis on the effect of personal selling and direct marketing on saving decisions yields a F test statistic of 416,739 with a probability of 0,000. (3) A t-test statistic of 4,695 with a probability of 0 is obtained from partial constant testing of the hypothesis on the decision to save. (4) A t-test statistic of 4,302 with a probability of 0 is obtained by testing the hypothesis partially on personal selling on saving decisions. (5) Testing partial direct marketing hypotheses on saving decisions yields a t-test statistic of 10,511 with a probability of zero. This researchers reported that (1) personal selling has a positive and significant effect on saving decisions. (2) that direct marketing has a significant and positive impact on saving decisions.